Self Confidence Pada Mahasiswa yang Aktif Berorganisasi dan Mahasiswa yang Tidak Berorganisasi di Kampus X - Firdaus Surya (Jurnal Sains Farmasi Dan Kesehatan, 2024)
Students who have various challenges while living their student life. Thus self-confidence becomes important for college students. College students' self-confidence needs to be formed through various activities on college, both activities in the classroom and other activities such as college student organizations. This research aims to find differences in self-confidence between students who are active and who are not active in organizations. This research used asimple random sampling with 116 respondents. This research shows that the self-confidence of students who are not active in organizations is higher with an mean 70.948, while the self-confidence of students who are active in organizations is lower with an mean 69.465. With these results it can be concluded that the self-confidence of students at campus X does not have any significant differences so that the visible aspects are not much different.